Trends in the analytical methods for the determination of trans fatty acids content in foods - Albuquerque, T.G. (2012)
Partially hydrogenated vegetable oils containing trans fatty acids (TFA) have been used in the food industry, due to its low cost compared with other fats and availability to extend the shelf-life of products, as well as to impart desirable characteristics to the food. A compilation of the available information on sample preparation and analytical methods for the determination of TFA in foodstuffs was the basis of the present extensive bibliographic review. This review contributes for a better understanding of the analytical approaches adopted to determine TFA and to follow the tendency over the years to enhance the knowledge toward TFA contents found in foodstuffs.